The level of understanding about the concept of REITs among investor / Muhammad Zuhair Ikram Othman. - Othman, Muhammad Zuhair Ikram (2019)
Real estate investment trust (REIT) is a mutual real estate investment scheme incorporating the best property and trust fund characteristics. The Malaysian Government released Guidelines for Islamic Real Estate Investment Trusts through the Securities Commission Malaysia (SC) in November 2005, setting a new global standard for the implementation of this method and making Malaysia the first jurisdiction to implement such guidelines in the industry. The problem is despite the use of I-REIT increasing, it has not yet achieved the awareness of this I-REIT among this country. This research is to study the level of understanding and also the awareness about the concept of REIT among investor. To complete the study three questions are created to achieve the objective of the study which are to identify the concept of REIT and I-REIT as the instrument of investment. Second, to investigate the advantages of REIT and I-REIT among investor and last but not least, to analyse the factor that influence investor behaviour towards REIT investment. In order to achieve the objective, questionnaire will be given to the participant of investment class led by Mr. Anas. The result of this study is most of the respondents are aware about the existence of i-REIT but some of the respondents still lack of information about the functionality and the advantages of i-REIT. Based on the result a several recommendations can be implemented to achieve Bank Negara Malaysia goals which is government should as a most suitable instrument to for the people.